Optimizing Onion Growth on Coastal Land: Evaluating Various Manure Types and Dosages - Mia, Ayu; Pujiwati, Hesti; Sumardi (BPFP Universitas Bengkulu, 2023)
The demand for onion in Indonesia has been on the rise. However, domestic production to date has not been able to meet all the needs of the people in Indonesia. This research aims to obtain the best type and dose of manure for the growth and production of shallots on coastal land. The design used in this research was a factorial Randomized Complete Block Design (RCBD) with 2 factors. The first factor is the type of manure which consists of 3 levels, namely: chicken manure, goat manure, and cow manure. The second factor is the dose of manure which consists of 4 levels, namely: 5, 10, 15, and 20 tons ha-1 . A total of 12 treatment combinations were derived from the two factors, each repeated 3 times to create 36 experimental units. The results showed that the interaction between several types and doses of manure had a significant effect on the variables of plant height and number of leaves at 2 WAP, 3 WAP, 4 WAP, 5 WAP, and 6 WAP. The optimum dose of manure was 20 tons ha-1 resulting in the highest average variable weight per plot of 142 g. The application of different types and dosages of manure did not significantly impact plant height, number of leaves, number of tillers, fresh weight of plants, fresh weight of tubers per hill, or weight per tuber.